Determination of Indium in Lettuce Samples Using Hydrogen Supported-T-cut-slotted Quartz Tube-atom Trap-flame Atomic Absorption Spectrometry - Kapukiran, Fatih; Yilmaz, Ozge; Tekin, Zeynep; Buyukpinar, Cagdas; Ozdogan, Nizamettin; Bakirdere, Sezgin (OXFORD UNIV PRESS, 2020)
In the present method, detection power of flame atomic absorption spectrophotometry (FAAS) was increased by utilizing a T-cut-slotted quartz tube (T-SQT) and combining with atom trap and hydrogen supported revolatilization (T-SQT-AT-FAAS) in order to determine indium at trace levels. Hydrogen gas instead of toxic organic solvents was provided to the system as reducing medium in order to release the atoms trapped on the inner walls of SQT. The method indicated a linear range between 10.0-150 mu g L-1 , and limit of detection and quantification (LOD/LOQ) values were calculated under the optimal conditions as 2.4 and 7.8 mu g L-1, respectively. A 1333 fold enhancement was achieved in the detection power of the conventional FAAS by 7.2 mL min(-1) sample/standard solution for 6.0 min period of trapping. Validity and applicability of the proposed determination system was checked in lettuce samples with spiking experiments. The results were satisfactory within the range of 91.0-106.7%. Recovery results represent the high accuracy of the method for the lettuce matrix, and %RSD was found to be 2.9% indicating the high precision.
Keywords: Flame atomic absorption spectrometry; Indium; Atom trap; GENERATION; CADMIUM; LEAD; PHOSPHIDE; RATS; Chemistry